Wheat Production - Gretchen Sassenrath; D. E. Shoup; R. Lollato (Kansas Agricultural Experiment Station Research Reports, 2017)
Wheat production in southeast Kansas is often limited due to high rainfall during the harvest. In some years, this high rainfall can exacerbate disease pressure, especially fungal infections. This study presents results from a test of fungicide applications to control Fusarium head blight (FHB) or scab in poor quality wheat.
Keywords: wheat; fungicide; fusarium head blight; fungal disease; wheat yield